Influence of suctioning on cardiac autonomic control of neonates after delivery: impact of birth weight - Larissa S. Sande; Deyse C. Porto; Ana Carolina B. Perrone; Ludmilla F.S. Campos; David Lomanto Couto; Jonas R.D. Silva; Rafael da Silva Passos; Alinne Alves Oliveira; Rafael Pereira (Hygeia Press di Corridori Marinella, 2022)
Background: Studies have explored the airway and/or gastric suctioning impact, but its influence on cardiac autonomic control (CAC) has not yet been investigated. Purpose: To investigate the influence of upper airway and/or gastric suctioning after delivery on CAC of neonates stratified according to weight for gestational age. Methods: A cross-sectional study was conducted with 100 healthy full-term newborns with up to 72 hours of life. The obstetric records were accessed to obtain maternal, delivery and newborn data, and neonates were stratified as small for gestational age (SGA), appropriate for gestational age (AGA), or large for gestational age (LGA). Neonates were also grouped according to the suctioning procedure performed after delivery (i.e., suctioned and not suctioned). Time-domain parameters were obtained from successive RR intervals and compared between suctioned and not suctioned neonates of each group (SGA, AGA, and LGA).  Results: SGA neonates who were suctioned exhibited significantly higher TRI RR and TINN values in the first 72 hours after delivery. Conclusions: The suctioning procedure seem to impact on the CAC only in SGA neonates, with better CAC in the first 72 hours of extrauterine life among suctioned SGA neonates.